2011
DOI: 10.1089/lap.2010.0572
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Ventral Hernia Repair: A Comparative Study of Transabdominal Preperitoneal Versus Intraperitoneal Onlay Mesh Repair

Abstract: Besides the cost-effectiveness of TAPP procedure, it reduces the risk of complication related to intra-abdominal position of mesh and fixating devices. Before we label the TAPP repair of ventral hernia as the first choice, a comparative multicentric prospective trial with IPOM repair is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 26 publications
2
36
1
2
Order By: Relevance
“…An experimental study in a sheep model showed that after placement of new‐generation coated mesh (Parietex® composite), the mean extent of adhesions increased over time without reaching a steady state within the first 12 months . Only a few studies have described the TAPP approach for umbilical hernia; they suggested that TAPP reduces the risk of complication related to the intraperitoneal position of the mesh and that it has a lower complication rate than the Intraperitoneal Onlay Mesh (IPOM) procedure . If coating mesh is covered with native biological tissue such as the peritoneum, it should form fewer adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study in a sheep model showed that after placement of new‐generation coated mesh (Parietex® composite), the mean extent of adhesions increased over time without reaching a steady state within the first 12 months . Only a few studies have described the TAPP approach for umbilical hernia; they suggested that TAPP reduces the risk of complication related to the intraperitoneal position of the mesh and that it has a lower complication rate than the Intraperitoneal Onlay Mesh (IPOM) procedure . If coating mesh is covered with native biological tissue such as the peritoneum, it should form fewer adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…10 The ergonomic features of the robot also give the surgeon the opportunity to create a peritoneal flap for preperitoneal mesh placement to prevent meshrelated intra-abdominal complications and reduce the risk of migration and lateral detachment, which are often cited as the cause of recurrence. 11,12 To date, there are no case reports on the use of the robotic platform to repair a nonmidline ventral hernia from a hand-assist site. We used the guidelines and principles set forth for repair of midline ventral hernias and literature on lateral hernia repair to guide us in our repair.…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons were the great technical di culty of the procedure and the long operative time. However, this situation has changed in the last 2 years, as many articles about this emerging technique from different countries have been published (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%